The Impact of Online Business on Malaysian Taxation - Sidik, Morni Hayati Jaafar (International Journal of Engineering and Technology, 2018)
Online business has transformed the way of conducting business and have raises several tax issues and problems internationally. Many tax authorities around the world felt that this communication revolution has created new possibilities for tax administrations to improve the efficiency of their operation but also open up new possibilities for tax evasion. They also viewed that the current taxing rules are insufficient to deal with online business. As more Malaysian companies and individuals involve in online business, they will also be exposed to this issue. The purpose of this paper is to study the tax issues and problems raised by the online business transactions from Malaysian perspectives. It also examines at the impact of online business on Malaysian taxation system. Finally, this paper will also discuss some possible solutions for the tax authorities to deal with the challenges posed by the online business.